SOSIALISASI PENGARUH KENAKALAN REMAJA DI DESA BUHO–BUHO, KECAMATAN MOROTAI TIMUR, KABUPATEN PULAU MOROTAI - Papuling, Oktadwilaras A.P; Ale, Gregorius Exel (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2025)
This Community Service Activity aims to provide knowledge for teenagers in Buho - Buho village, about the influence of juvenile delinquency including knowledge of juvenile delinquency, the impact of delinquency on teenagers and examples of juvenile delinquency in everyday life. The activity was carried out in Buho - Buho Village, Morotai Island, for 1 day. The method used in this community service activity was socialization about the influence of juvenile delinquency followed by questions and answers by teenagers in Buho - Buho village. The results of the activity showed that the participants' knowledge, which includes knowledge to distinguish between good and bad behavior, knowledge about the impact of juvenile delinquency, and examples of juvenile delinquency that often occur in everyday life.